Treatment of patients with acute promyelocytic leukemia using AIDA regiments: 20 years long single center experience - Mitrovic, Mirjana; Sabljic, Nikica; Pantic, Nikola M; Trajkovic, Lazar; Bukumiric, Zoran; Virijevic, Marijana; Pravdic, Zlatko; Jakovic, Ljubomir; Jovanovic, Jelica; Kraguljac Kurtovic, Nada; Milosevic, Violeta; Rajic, Jovan; et al. (Medical Research, 2025)
Introduction: The introduction of all-trans retinoic acid (ATRA) has transformed acute promylocitic leucaemia (APL) from a highly fatal to a curable disease. However, a significant frequency of early death (ED) and relapse represents challenges in everyday practice. The aims of this study are to report our 20-year-long experience using AIDAbased protocols and to assess the predictive value of clinical and laboratory parameters for ED/relapse development. Material and methods: This retrospective study included patients treated at the Clinic for Hematology, UKCS, in the period 2004-2024. RS was defined as death within the first 30 days of hospitalization. Results: 158 patients were included. ED and relapse occurred in 38/158 (24%) and 15/119 (12.6%) patients. ED rate stayed stable through time (2004-2008 period 20.6%, 2009–2013 21.9%, 2014–2018 23.1%, 2019– 2024 27%) with bleeding as the most frequent cause (42%), followed by DS (24%) and infection (16%). Final predictors for ED development were ISTH DIC score (p=0.008, OR 2.380, 95% CI 1.249-4.533), aPTT (p=0.009, OR 0.786, 95% CI 0.656-0.941), ECOG PS (p=0.000, OR 2.964, 95% CI 1.630-0.988). Predictors for relapse were: ECOG PS ≥ 3 1(21.7% vs 78.3%, p=0.019) and bcr3 PML-RARA transcript (29.6% vs 70.4%, p=0.046). Conclusion: Our experience showed a very high rate of ED, with haemorrhage, DS and infection as a main reason. Preventive strategies should include comprehensive medical education, regarding prompt recognition, appropriate early transfusion support therapy, and the rapid initiation of ATRA. Patients with high ECOG PS and ISTH DIC score probably need different coagulation monitoring and reinvented therapy.